Relationship of relevant factors to P(v-a)CO2/C(a-v)O2 ratio in critically ill patients. Issue 1 (January 2020) - He, Huaiwu; Long, Yun; Liu, Dawei; Tang, Bo; Ince, Can
Objective: This study investigated the factors related to the ratio of the venoarterial carbon dioxide tension difference [P(v-a)CO2 ] to the arteriovenous oxygen content difference [C(a-v)O2 ] (hereafter termed "Ratio"). Methods: We retrospectively studied 1294 pairs of arterial and central venous blood gas measurements in 352 critically ill patients. A high Ratio was defined as > 1.68 based on published literature. Measurements were divided into four groups: Group I [P(v-a)CO2  ≤ 6 mmHg/central venous oxygen saturation (ScvO2 ) < 70%], Group II [P(v-a)CO2  ≤ 6 mmHg/ScvO2  ≥ 70%], Group III [P(v-a)CO2  > 6 mmHg/ScvO2  ≥ 70%], and Group IV [P(v-a)CO2  > 6 mmHg/ScvO2  < 70%]. Results: The Ratio's strongest correlation was with P(v-a)CO2 when compared with ScvO2 and hemoglobin in all data. The P(v-a)CO2 and ScvO2 were significantly higher and the hemoglobin and arterial oxygen saturation were significantly lower in the high Ratio measurements (>1.68) than low Ratio measurements (≤1.68). The P(v-a)CO2 was best for predicting a high Ratio. A P(v-a)CO2 threshold of 7 mmHg was associated with a sensitivity of 41.77% and specificity of 90.62% for predicting a high Ratio. Conclusions: A high P(v-a)CO2 is the most relevant contributor to a high Ratio among all related factors in critically ill patients.